The HR 4.0 Revolution: Unraveling the Link Between HRM Digitalization, Employee Stability, and Supply Chain Resilience (An Explanatory Study at PT Astra Honda Motor Binjai Branch) - Siswa Pratama (CERED Indonesia Institute, 2025)
In the hyper-competitive automotive industry ecosystem, distribution branches become the frontline vulnerable to shocks, including those caused by human resource (HR) fluctuations. High turnover intention is no longer just an HR problem, but a systemic threat to operational continuity and supply chain resilience.This study holistically dissects the strategic role of Human Resource Management (HRM) digitalization as a tool to strengthen employee retention, and how the resulting HR stability acts as a catalyst for improving work productivity and Supply Chain Management (SCM) performance. Using a qualitative explanatory case study approach at PT Astra Honda Motor (AHM) Binjai Branch. Data was collected through triangulation: in-depth interviews with 7 informants from strategic to operational levels, participant observation, and analysis of performance documents (2020-2023). Data was analyzed using thematic analysis techniques. The implementation of an integrated HRIS (covering e-recruitment, e-learning, digital performance appraisal, and employee self-service) successfully created a virtuous cycle. Digitalization fostered perceptions of procedural fairness, career transparency, and service efficiency, which significantly reduced turnover intention by up to 15%. This HR stability directly impacted: (1) Operational Productivity: A 12% increase in Overall Equipment Effectiveness (OEE) in the warehouse area; (2) SCM Performance: An 8% surge in on-time delivery to dealers and a 10% decrease in error rate in spare parts handling. HRM digitalization is proven to be not merely an administrative efficiency project, but a strategic investment in building resilience. By stabilizing the